Comprehensive Review of Cultural Influences, Ethical Dimensions, And Policy Adaptations in Global Healthcare - Almas, Abdullah Musleh Ali; AlAbdullah, Tahani Ali Salem; Alqahtani, Amal Mushabbab S; Alyami, Thuraya Samran Jahal; Al Zaid, Saleha Hadi Ahmad; Al masad, Hagsa Salman Masad; alyami, Wefgah Salem jmaan; Alkiran, Tagwa Hadi Masfer; Al Daghman, Hussain Abdulhadi; Alyami, Wafgah Mubarak Masoud (Journal of Ecohumanism, 2024)
Today, culture, ethics, and policies play a significant role in the configuration of the global health system. Given diverse populations, organizational culture, ethics, and rapid technological advancements, global health crises have become important for functional healthcare systems in deciding the quality of healthcare services. This review synthesizes options to determine the social-cultural influence on health behavioral practice, ethical dilemmas in practicing health care, and policy solutions. This heuristic paper assesses these elements and speculates on their consequences for world health systems.